If They Endorse It, I Can't Trust It: How Outgroup Leader Endorsements Undercut Public Support for Civil War Peace Settlements. Issue 4 (29th April 2020) - Haas, Nicholas; Khadka, Prabin B.
Abstract: Civil wars are a greater source of violence than any other type of conflict, yet little is known about one of the key determinants of civil war peace settlement success: civilian support. We evaluate how a core component of nearly all peace settlements, leader endorsements, affects public support. We predict that individuals in conflict settings will view settlements endorsed by outgroup leaders as less trustworthy and that they will become less supportive. We conduct an endorsement experiment with nearly 1, 000 respondents in South Sudan in 2016, taking advantage of a brief cessation in a devastating civil war. Public support for a tentative settlement drops precipitously when it is endorsed by an outgroup leader but does not increase when it is endorsed by an ingroup leader. We find suggestive evidence that effects are strongest for individuals with the greatest reason to fear outgroup leaders: those whose communities were targeted most violently by that outgroup.